Impact of defects in self-assembled monolayer on humidity sensing by molecular functionalized transistors. (13th April 2020) - Tanaka, Takahisa; Yajima, Takeaki; Uchida, Ken
Abstract: For highly sensitive and selective sensors, numerical study of transistors functionalized with a defected self-assembled monolayer (SAM) was performed. Adsorption of water molecules on the defected SAM was treated by molecular dynamics (MD) calculations. Based on time dependent atomic positions and charges derived from the MD calculations, carrier concentration and threshold voltage of defected-SAM-functionalized transistors were derived from the Poisson equation. The defects of the SAM caused a penetration of water molecules. Due to a strong polarization of water molecules, the water molecules penetrating the defects were stacked in the same direction. The alignment of the water molecules in the defects generated a large electrical dipole, and the threshold voltage of the transistors were shifted.